MR guided cardiac ablation: how to build an interventional magnetic resonance suite and what's the role of the imaging. (26th April 2023) - Fusco, Armando; De Ruvo, Ermenegildo; Stefanini, Matteo; Borrelli, Alessio; Ferrazza, Alessandro; De Luca, Lucia; Simonetti, Giovanni; Calò, Leonardo
Abstract: Magnetic resonance (MR) represents a new interesting imaging approach for guiding electrophysiology (EP)-based ablation procedures of atrial flutter and typical atrial fibrillation. This new approach permits to reach good results if compared with conventional EP ablation. Tissue characterization by MR permits to detect cardiac anatomy and pathological substrate like myocardial scars well visualized with late gadolinium enhancement (LGE) sequences. Intra-procedural imaging is useful to real-time follow the catheter during the ablation procedure and at the same time to visualize cardiac anatomy in addition to understanding if the ablation is correctly performed using oedema sequences. Performing cardiac ablations inside an MR room permits to reduce radiation exposure and occupational illnesses.